Primary School Teachers Preparedness in Performing Online Learning: The Case of Teachers in Jakarta Area: Kesiapan Guru Sekolah Dasar dalam Melaksanakan Pembelajaran Daring: Studi Kasus Guru di Wilayah Jakarta - Nurafni; Dadan Dasari; Dadang Juandi; Yaya Sukjaya Kusuma; Turmudi; Al Jupri (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Teachers do not simply conduct online or remote learning by delivering materials to learners, but rather through optimal preparation to ensure effective implementation. The shift to long-distance learning during the Covid-19 pandemic required teachers to master their subject matter, align personal interests and talents with educational goals, and demonstrate a positive professional attitude. This study aimed to determine the readiness of primary school teachers in implementing online learning during the Covid-19 pandemic. Using a quantitative survey design, the research was conducted in primary schools across the Jakarta metropolitan area (Jakarta, Bogor, Depok, Tangerang, Bekasi). Participants (n=280) were selected using a combination of random and convenience sampling techniques. Data were collected using the Teacher Readiness for Online Learning Measurement (TROLM) instrument developed by Ming Hu in 2015 and analyzed using percentage calculations. The results showed that teachers demonstrated emotive attitudinal readiness of 54.4%, cognitive readiness of 55.9%, and behavioral readiness of 51.5%, indicating that overall, they are well-prepared to implement online learning. Based on these findings, it is recommended that continuous professional development, adequate digital infrastructure, and sustainable policy guidelines be provided to further enhance teachers’ digital pedagogical competencies and ensure the long-term effectiveness of online learning beyond the pandemic context